Diagnosis and Treatment of Manifestations of Endothelial Dysfunction in ICU Patients with Severe Acute Pancreatitis - V. V. Kiselev; M. S. Zhigalova; S. S. Petrikov; E. V. Klychnikova; P. A. Yartsev (Неотложная медицинская помощь)
BACKGROUND. Acute pancreatitis is an aseptic inflammation of the demarcation type based on necrosis of pancreatic acinar cells, and enzymatic aggression, followed by expanding necrosis and dystrophy of the gland, in which damage to surrounding tissues, as well as distant organs and systems, and the addition of a secondary purulent infection are possible. An important pathogenetic aspect of the severe course of acute pancreatitis is endothelial dysfunction. The latter often begins as a diffuse activation of coagulation, which further potentiates the progression of the systemic inflammatory response syndrome and, thereby, complicates the course of acute pancreatitis. There is a connection between the activation of coagulation and the severity of inflammation. Traumatic tissue injury, followed by hypoperfusion, hemodilution, hypothermia, and acidosis cause acute post-traumatic coagulopathy. The inflammatory process activates the coagulation system, reduces the activity of natural anticoagulants and disrupts the functioning of the fibrinolytic system, thereby leading to thrombosis.   AIM OF STUDY. Improving the results of treatment of patients with severe acute pancreatitis by choosing the optimal method of extracorporeal hemocorrection and anticoagulant therapy.   MATERIAL AND METHODS. The present retrospective-prospective study included 76 patients (50 (65.7 %) men and 26 (34.2 %) women) diagnosed with severe acute pancreatitis. To assess the effectiveness of the therapy, the patients were divided into 2 groups: the control group (n=34), based on the retrospective analysis of case histories, included patients who received standard conservative therapy. The severity of the condition was assessed using APACHE II, SOFA, MARSHALL and Ranson scales, and amounted to 16.8 ± 4.2, 3.44 ± 1.32, 2.6 ± 0.64, 3.8 ± 0.52 points, respectively. The main group (n=42) included patients whose treatment was supplemented with the use of low molecular weight heparin preparations, extracorporeal methods of hemocorrection with the inclusion of cytokine adsorption together with renal replacement therapy. The severity of the condition of the 2nd group’s patients was assessed using APACHE II, SOFA, MARSHALL and Ranson scales, and amounted to 16.6 ± 3.4, 3.26 ± 1.24, 2.5 ± 0.72, 3.6 ± 0.48 points, respectively.   CONCLUSION. As a result of expanded therapeutic tactics for severe acute pancreatitis (SAP) using sorption methods of extracorporeal hemocorrection, anticoagulant therapy with low molecular weight heparin, as well as the inclusion of saline enteral solution in the therapeutic regimen to restore intestinal propulsive function, it was possible to reduce the number of purulent-septic complications by 1.6 times, cases of development of multiple organ failure by 1.5 times, and mortality by 1.7 times.